2002
DOI: 10.1016/s0015-0282(01)02957-0
|View full text |Cite
|
Sign up to set email alerts
|

VAMP/synaptobrevin as an acrosomal marker for human sperm

Abstract: Objective:To determine the possible use of the mammalian acrosomal marker vehicle-associated membrane protein (VAMP)/synaptobrevin to detect acrosome abnormalities in human sperm. Design: Analysis of human sperm after fixation and staining with an anti-VAMP antibody. Setting: An academic research institution. Patient(s): Semen samples from consenting patients who were participating in an infertility treatment program. Intervention(s): Human sperm samples were fixed, permeabilized with detergent, and examined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Our previous study confirmed that monoclonal antibodies against intra-acrosomal sperm proteins are valuable and sensitive markers for the evaluation of sperm quality [15-20]. A correlation between sperm quality and fertility has been demonstrated using animal and human pathological spermatozoa [18-22] and also by our own results (prepared for publication). We can conclude that although spermatogenesis was established in the P generation, NP had an effect on sperm quality.…”
Section: Discussionsupporting
confidence: 83%
“…Our previous study confirmed that monoclonal antibodies against intra-acrosomal sperm proteins are valuable and sensitive markers for the evaluation of sperm quality [15-20]. A correlation between sperm quality and fertility has been demonstrated using animal and human pathological spermatozoa [18-22] and also by our own results (prepared for publication). We can conclude that although spermatogenesis was established in the P generation, NP had an effect on sperm quality.…”
Section: Discussionsupporting
confidence: 83%
“…Globozoopermia (round-head spermatozoa) is a familial disorder characterized by the production of abnormally round heads and non-fusiform motile spermatozoa (Schill 1991;Wolff et al 1976). Round-head spermatozoa are incapable of fertilizing oocytes, and in extreme cases, the acrosome is absent (Aitken et al 1990;Ramalho-Santos et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, all of these studies show that proacrosomal vesicles form and fuse to give rise to the acrosomal vesicle whether or not it is attached to the nucleus (Anton Lamprecht et al, 1976; Baccetti et al, 1977; Dam, Koscinski, et al, 2007; Perrin et al, 2013; Schirren, 1971). This may explain why round‐headed spermatozoa in the ejaculate may contain a few acrosomal vesicles around the nucleus (Dam, Koscinski, et al, 2007; Ramalho‐Santos et al, 2002; Singh, 1992).…”
Section: The Round‐headed Spermatozoamentioning
confidence: 99%